Spatially controlled lateral heterostructures of graphene and transition metal dichalcogenides toward atomically thin and multi-functional electronics. Issue 9 (21st February 2020) - Kim, Gwangwoo; Shin, Hyeon Suk
Abstract : This review demonstrates growth and electronic applications of lateral heterostructures of graphene and TMDs, highlighting key technologies controlling wafer-scale growth of continuous films for practical applications. Abstract : Edge contacts between two-dimensional (2D) materials in the in-plane direction can achieve minimal contact area and low contact resistance, producing atomically thin devices with improved performance. Particularly, lateral heterojunctions of metallic graphene and semiconducting transition metal dichalcogenides (TMDs) exhibit small Schottky barrier heights due to graphene's low work-function. However, issues exist with the fabrication of highly transparent and flexible multi-functional devices utilizing lateral heterostructures (HSs) of graphene and TMDs via spatially controlled growth. This review demonstrates the growth and electronic applications of lateral HSs of graphene and TMDs, highlighting key technologies controlling the wafer-scale growth of continuous films for practical applications. It deepens the understanding of the spatially controlled growth of lateral HSs using chemical vapor deposition methods, and also contributes to the applications that depend on the scale-up of all-2D electronics with ultra-high electrical performance.